wakalah WAKALAH BI AL-ISTISMAR SEBAGAI SOLUSI INVESTASI - Sholihah, Nurlailiyah Aidatus; Nurcahyati, Mely; Suhendar, Fikry Ramadhan (International Conference on Islamic Studies, 2023)
This paper aims to analyze the urgency of the wakalah bi al-istismar contract in increasing investment. Wakalah bi al-istismar is a representative agreement carried out to make investments in certain fields. This research method uses qualitative methods with literature study as the approach. The data source is in the form of literature publications related to wakalah bi al-istismar. The type of data is in the form of written narratives or documents contained in publication sources related to investment and wakalah bi al-istismar. The data collection technique was carried out by tracking sources of publications related to wakalah bi al-istismar. The data analysis technique is descriptive, namely explaining the wakalah bi al-istismar contract and then analyzing it regarding the urgency of the contract in investment. This article finds that the wakalah bi al-istismar agreement can be a solution for novice investors who do not yet have expertise in the field of company analysis or investment they are pursuing. Wakalah bi al-istimar is carried out by the investor giving authority to the investment manager to invest the amount of funds authorized by him. Thus, the investment manager has full control over the investment funds under his control.